La Région : une notion ambigüe saisie à travers le cas normand - Arnaud Brennetot; Sophie DE RUFFRAY (L'Espace Politique)
Focusing on Normandy, this paper intends to show that French “regions” are ambiguous realities, despite the efforts of institutionnalisation made since fifty years. The notion of “region” is actually associated to heterogeneous meanings that reduces its ability to be grasped by various stakeholders involved in their politicisation (political elites, journalists, citizens). A survey conducted in Normandy about the way elected officials perceive their region reveals that the various significations of the French “region” refer to disconnected spatial frameworks, generating deep and lasting confusions and geopolitical contradictions. Recurrent debates about a possible fusion of the “regions” Basse-Normandie et Haute-Normandie provides a significative example of existing ambiguities and deadlocks.